An Untethered Soft-Swallowing Robot with Enhanced Heat Resistance, Damage Tolerance, and Impact Mitigation - Haili Li; Xingzhi Li; Pan Zhou; Jiantao Yao (Chinese Journal of Mechanical Engineering)
Abstract Soft robotics focuses on addressing the locomotion problem in unstructured environments and the manipulation problem of non-cooperative objects, which inevitably leads to soft robots encountering multiple uncertainties and damages. Therefore, improving the robustness of soft robots in hostile environmental conditions has always been a challenge. Existing methods usually improve this robustness through damage isolation, material elasticity, and self-healing mechanisms. In contrast to existing methods, this paper proposes a method to improve the robustness of an untethered soft-swallowing robot based on the physical properties of fluids, such as the high specific heat capacity of water, the viscosity of soft glue, and the shear thickening of non-Newtonian fluids. Based on this method, we developed a soft-swallowing robot with enhanced heat resistance, damage tolerance, and impact mitigation capability by only replacing its fluid working medium. Experiments show that the developed soft-swallowing robot can withstand high temperatures above 600 °C, maintain high performance even after enduring hundreds of damages, and protect grasped object from more than 90% of external impacts. This principle extends beyond the three fluids used in this study. Other fluids, such as magnetic fluid, can increase adhesion to metal materials, whereas oily fluids can reduce frictional resistance between soft structures. Additionally, other solid materials with elasticity and compliance can serve as alternative working mediums for the soft-swallowing robot. This work contributes an effective method for fluid-dependent soft robotic systems to resist the damage from uncertain factors in harsh environments.